The German Logic of Emancipation and Biesta's Criticism of Emancipatory Pedagogy. Issue 6 (24th February 2022) - Moilanen, Antti; Huttunen, Rauno
ABSTRACT: Gert Biesta has criticized Anglo‐American and German models of emancipatory education. According to Biesta, emancipation is understood in these models as liberation that results from a process in which a teacher transmits objective knowledge to his or her students and cultivates student capabilities. He claims that this so‐called modern logic of emancipation does not lead to freedom because it installs inequality, dependency, and mistrust in the pedagogical relationship. In this article, Antti Moilanen and Rauno Huttunen analyze whether German models of emancipatory education share the modern logic of emancipation and if they can escape Biesta's criticisms. For this purpose, they interpret Biesta's critique of the modern logic of emancipation and explicate central ideas related to the German models of critical education. They also compare the modern logic of emancipation to the German one, and they then assess German models of emancipatory pedagogy from the viewpoint of Biesta's criticisms. Moilanen and Huttunen conclude that the German models of emancipatory education present at least a partial alternative to the modern logic of emancipation. Despite this, the German models are based on the idea of education as cultivation. Because Biesta criticizes the theory of education as cultivation, it is possible to conclude that he would not accept the German models of emancipatory education. However, the German models of critical pedagogy provide answers to the following question: how can students achieve independence in the pedagogical relationship? When students take part in designing educational processes, they are summoned to assess the validity of the taught knowledge, and they practice independent decision‐making at school; the pedagogical relationship, based on authority, can foster student self‐determination.